Feed consumption, growth and protein utilization of Colossoma macropomum (Cuvier) at different dietary fish meal/soya meal ratios - van der Meer, M B (1996)
The effect of a gradual substitution of dietary fish meal protein by soya meal protein on growth, feed uptake and protein utilization of 1 g Colossoma macro pomum (Cuvier) was studied at two different dietary protein levels. Growth rates of fish fed ad libitum 20 and 45% protein diets fluctuated between 41 and 49, and between 60 and 68 gkg-"" day-', respectively. Fish incorporated between 31 and 47% of the dietary protein in their body. Increased amounts of soya meal in the diet led to decreased feed uptake, higher body protein levels, lower ash levels and increased NPU values. If the low ash contents in the fish fed 100% soya diets are not prejudicial for health and growth of the fish in the long term, soya meal must be considered a superior protein source for C. macropomum. The high growth and the efficient use of the dietary protein indicate the C. macropomum is able to utilize soya protein more efficiently than other fish species.